The epidemiology of food allergy in Europe: a systematic review and meta‐analysis. Issue 1 (11th November 2013) - Nwaru, B. I.; Hickstein, L.; Panesar, S. S.; Muraro, A.; Werfel, T.; Cardona, V.; Dubois, A. E. J.; Halken, S.; Hoffmann‐Sommergruber, K.; Poulsen, L. K.; Roberts, G.; Van Ree, R.; et al.
Abstract Food allergy (FA) is an important atopic disease although its precise burden is unclear. This systematic review aimed to provide recent, up‐to‐date data on the incidence, prevalence, time trends, and risk and prognostic factors for FA in Europe. We searched four electronic databases, covering studies published from 1 January 2000 to 30 September 2012. Two independent reviewers appraised the studies and qualified the risk of bias using the Critical Appraisal Skills Programme tool. Seventy‐five eligible articles (comprising 56 primary studies) were included in a narrative synthesis, and 30 studies in a random‐effects meta‐analysis. Most of the studies were graded as at moderate risk of bias. The pooled lifetime and point prevalence of self‐reported FA were 17.3% (95% CI: 17.0–17.6) and 5.9% (95% CI: 5.7–6.1), respectively. The point prevalence of sensitization to ≥1 food as assessed by specific IgE was 10.1% (95% CI: 9.4–10.8) and skin prick test 2.7% (95% CI: 2.4–3.0), food challenge positivity 0.9% (95% CI: 0.8–1.1). While the incidence of FA appeared stable over time, there was some evidence that the prevalence may be increasing. There were no consistent risk or prognostic factors for the development or resolution of FA identified, but sex, age, country of residence, familial atopic history, and the presence of other allergic diseases seem to be important. Food allergy is a significant clinical problem in Europe. The evidence base in this area would benefit from additional studies using standardized, rigorous methodology; data are particularly required from Eastern and Southern Europe.